The choice of word-reaction by people who react quickly and slowly - Elijošiūtė, S. (Psichologija, 1984)
From the data of the free word association experiment with a thousand people a group of quick reaction (184 people) and a group of slow reaction (171 people) were distinguished. The juxtaposition of the data of the two groups and of each group with the general count makes it possible to draw the following conclusions: 1) there are no significant differences in the choice of lexemes-reactions either in the group of quick or in the group of slow reaction as compared with the general data; 2) the group of slow reaction as compared with the group of quick reaction gives paradigmatic associations mare often (by approximately 20 percent).